Concept of posi: symbol and sacred space of Luwu architecture - Sutrisno, Moh.; Sahabuddin, Wasilah (2025)
Chiefdom buildings, Langanae, Salassae, places for making weapons, places for valuable and historical items, and mausoleums have important values in the Islamic architectural civilization in Tana Luwu. Lokkoe is one of the Luwu Chiefdom areas filled with mausoleums (king's tombs). The typology of the mausoleum building is unique and has relationships with similar objects in other areas in South Sulawesi. Syntactic relations exist between the chiefdom building, the Luwu chiefdom palace complex gate, and the Lokkoe gate. However, the Lokkoe Area authorities allowed the chiefdom's mausoleum to appear unkempt, unsacred, and unsafe. The research uses qualitative methods with a symbolic interactionism paradigm. The research results show that Lokkoe Architecture is representative. The Lokkoe area is a tana tekko area, which is the upper layer and sacred space in the urban space layer. The Lokkoe area has symbols of social strata manifested by the gate and the unique shape of the mausoleum. The center of space symbolically forms the structure of space and cosmological symbols. Lokkoe and its context have a syntactic relationship with similar tombs in South Sulawesi, while the chiefdom context tends to be related to Malay architecture in the archipelago. Lokkoe architecture has the potential to become an architectural icon like the Taj Mahal. It can become a cultural tourist attraction in Tana Luwu, South Sulawesi, Indonesia, and the archipelago.